Perancangan Sistem Informasi Persediaan Produk Kaos Berbasis Metode Period Order Quantity (Study Kasus: PD.Teguh Kaos Polos) - Taufik, Ujang Arif; Putro, Bramantiyo Eko (Universitas Suryakancana, 2018)
Economic growth causes goods and services produced to increase and competition in the process of meeting the needs of consumers. PD.TEGUH KAOS POLOS is a trading company engaged in the field of clothing. The existing problem is the stockpile of goods that cause large inventory and not necessarily when the time of purchase of raw materials and the process of recording transactions, whether the purchase transactions and sales transactions are still using the manual with a note and ledger. The purpose of this study to determine the economic order and frequency of optimal ordering time by using Period Order Quantity method with the help of management information system design to help find out the information system needs regarding the amount of stock available. POQ calculation results obtained that the optimal order amount of 1803 units / pcs with the frequency of ordering 11 times and the distance between reservations for 29 days. There was a decrease in stock buildup around 7626 units / pcs. POQ decreases message costs and saves Rp.36.171.103 which can save company costs. Functionally a company needs a computerized information system and non-functional companies need a computer device CPU with the help of XAMPP software to run the database. With inventory information system using POQ saves working time to be more effective and efficient.